REREAD THE PUBLIC: The New and Future Public Relations - Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
The communications revolution, marked by developments in information technology, changes in the media ecosystem and audience habits, and an increasingly open communications culture and climate, is forcing public relations (PR) and corporate communications professionals to change their mindsets and work patterns. Public relations leadership requires a rereading of the meaning of 'public.' How companies and organizations run also requires adjustments to new paradigms, which has consequences for how PR leadership adapts. This article examines changes in professional organizations and public relations strategies. Some of them include a paradigm shift from corporate brand image to corporate brand engagement, from corporate identity to corporate behavior, superiority to equality, snobbery to humbleness, from regular to adaptive and creative PR, from insensitive to empathetic PR, from objective to subjective PR, from mechanistic/normative to humanistic PR, and from digital to digital-humanistic PR. How to cite this article:Wijaya, B. S. (2019). Reread the Public: The New and Future Public Relations. Journal Communication Spectrum: Capturing New Perspectives in Communication, 9(1), 79-93.